A kolozsvári példa dokumentumok a kolozsvári egyetemi menza működéséről és debreceni kapcsolatáról - Király, Sándor (Gerundium, 2017)
In the Footsteps of Kolozsvár. Documents on Students Work at the University of Debrecen and its Connection with the University of Kolozsvár. It’s a well-known historical fact that the foundation of the students’ canteen in the University of Debrecen was one of the first steps to establish a welfare organization in a hope to support hundreds of students in their studies between the two World Wars in Debrecen. Also widely known that under the guidance of Nándor Láng this students’ canteen gained prosperity. At thesame time, far less attention has been given to networks and relations in higher education underpinning this initiative. Láng asked assistance and information from the University of Kolozsvár which was the only provincial university in Hungary. The letter of Béla Posta which was written to Nándor Láng in December 20, 1916 and all of the attached documents are very rare and valuable sources of the history in both universities. The paper therefore can be considered as a novelty by giving an insight into the partnership of the University of Debrecen and Kolozsvár.